The Association Between Craniovertebral Angle and Neck Muscle Size Using Ultrasonography: A Systematic Review - Fatemeh Binaei; Amir Hossein Kahlaee; Mohammad Ali Mohseni Bandpei; Nahid Rahmani; Cyrus Taghizadeh Delkhoush; Mohammad Saatchi (Health Science Reports)
ABSTRACT Background and Aims Using ultrasonography to systematically review all published studies that investigated the association between craniovertebral angle (CVA) and neck muscle size. Methods This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Searches were performed in PubMed, Science Direct, OVID, MEDLINE, and Google Scholar databases from January 2000 to October 2024. The keywords used were: “Forward head posture,” “Cranial vertebral angle,” “size,” “thickness,” “weakness,” “enlargement,” “hypertrophy,” “ultrasonography*,” “Diagnostic ultrasound,” “ultrasonic imaging,” “imaging,” “medical sonography,” and “ultrasonic diagnostic”. Results Of the 329 articles retrieved from the databases, 10 studies fulfilled the inclusion criteria. Four studies investigated the size of neck flexor muscles, four articles investigated the size of neck extensor muscles, and two articles focused on the size of both neck flexor and extensor muscles. Six studies compared participants with and without forward head posture (FHP). Two studies were conducted among asymptomatic subjects, while the other two studies were conducted among participants with and without neck pain. Consistent evidence supported that a significant correlation between the CVA and the thickness of deep neck flexor muscles (n = 1), a significant correlation between FHP and the thickness of the splenius capitis muscle (n = 1), an increase in sternocleidomastoid (SCM) muscle thickness (n = 2) and a decrease in semispinalis capitis (SSC) muscle thickness (n = 1) in subjects with FHP compared to those without, and a decrease in semispinalis capitis muscle thickness in individuals with FHP accompanied by neck pain compared to those with FHP without neck pain (n = 1). Conclusion The reviewed studies demonstrated that changes in the CVA are associated with alterations in neck muscle size, particularly affecting the SCM and SSC muscles. Additional research is necessary to investigate the functional implications of alterations in muscle characteristics.